Pharmacokinetic study of methylnaltrexone after single and multiple subcutaneous administrations in healthy Chinese subjects. (3rd August 2018) - Zhang, Dan; Ma, Jing-Yi; Yang, Man; Deng, Ming; Liu, Huichen
Abstract: 1. Pharmacokinetics of methylnaltrexone (MNTX) were evaluated after subcutaneous administrations (s.c.) in healthy Chinese subjects. 2. In a cross-over single dose study, 12 subjects were given 0.075, 0.15, and 0.3 mg/kg of MNTX bromide injection. In a multiple doses study, another 12 subjects subcutaneously received 0.15 mg/kg of MNTX bromide injection every 48 h, in total five administrations. The concentrations of MNTX in plasma were quantified by LC–MS/MS. 3. After single s.c. administrations of 0.075, 0.15, and 0.3 mg/kg of MNTX bromide, C max values of MNTX were 93.5 ± 28.6, 191 ± 37, and 364 ± 54 ng/mL, respectively, and AUC0–∞ were 88.8 ± 8.8, 181 ± 16, and 357 ± 34 ng⋅h/mL, respectively. The t 1/2 of MNTX was about 7.7 h. After multiple doses administration, the C max, C av, AUCss, and MRT0–∞ values were 191 ± 50, 3.79 ± 0.40 ng/mL, 182 ± 19 ng⋅h/mL, and 3.56 ± 1.17 h, respectively. 4. Methylnaltrexone bromide displayed dose-proportional pharmacokinetics in the dose range of 0.075–0.3 mg/kg. After multiple doses administration, t 1/2 was slightly prolonged, with the cumulative factor of 1.02. This study provides a pharmacokinetic reference after a single dose and multiple doses of MNTX bromide in Chinese subjects.